PENGARUH DIGITAL MARKETING DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN BERKUNJUNG (Studi Kasus Pada Wisata Kampoeng Durian Bengkulu Tengah) - Sisi Sumatri; Muhamad Galy Njoman Ari Pribowo (UM. Bengkulu, 2023)
This study aims to determine the effect of digital marketing and service quality on the decision to visit Kampoeng Durian Bengkulu Tengah tourism, either partially or simultaneously. The sample in this study was 170 respondents, the data collection method used was Accidental Sampling. Data collection techniques with observation and questionnaires, data analysis techniques with multiple linear regression.The tcount value for the Digital Marketing variable for the Digital Marketing variable is 4.869 and a sig value of 0.000 <0.050, which means that there is a positive influence between Digital Marketing and the Decision to Visit Kampoeng Durian Bengkulu Tengah Tourism. The tcount value for the Service Quality variable is 7.164 and the sig value is 0.000 <0.050, which means that there is a positive influence between Service Quality on the Decision to Visit Kampoeng Durian Bengkulu Tengah Tourism. Based on the results of calculations using SPSS, to test the coefficients as a whole, the F test is used using a significant level of 0.05 to obtain a Fsig of 0.000 while the calculated F value is 68.820, so it can be interpreted that Fsig < Î± (0.000 < 0.050) this shows that Ho rejected and Ha accepted thus overall the influence variables namely Digital Marketing and Service Quality have a significant and positive influence on the Decision to Visit Kampoeng Durian Bengkulu Tengah Tourism. Keywords: Digital Marketing, Service Quality and Purchasing Decisions